2020
DOI: 10.1051/0004-6361/202037908
|View full text |Cite
|
Sign up to set email alerts
|

A wide angle view of the Sagittarius dwarf spheroidal galaxy

Abstract: We report on the discovery and chemical abundance analysis of the first CEMP-r/s star detected in the Sagittarius dwarf spheroidal galaxy (Sgr dSph) by means of UVES high-resolution spectra. The star, found in the outskirts of Sgr dSph, along the major axis of the main body, is a moderately metal-poor giant (Teff = 4753 K, log g = 1.75, [Fe/H] = −1.55) with [C/Fe] = 1.13, placing it in the so-called “high-carbon band”, and strong s-process and r-process enrichment ([Ba/Fe] = 1.4, [Eu/Fe] = 1.01). Abundances of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 95 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Gull et al (2018) claimed that this object was the first bona fide CEMP-r+s star as its abundance pattern could be satisfactorily fitted only with AGB mass-transfer model taking into account initial r-process enhancement. Sbordone et al (2020) reported the abundance analysis of object GIU J190734.24-315102.1 located in the Sagittarius (Sgr) dwarf spheroidal (dSph) galaxy, and claimed that the abundance pattern could be best fit only with a model considering AGB-pollution in a binary system preenriched with a neutron star-neutron star merger event. Sbordone et al (2020) classify this object as the first CEMP-r/s star found in the Sgr dSph, but due to its formation scenario this object may be referred to as a bona fide CEMP-r+s star.…”
Section: Agb and Accretion-induced Collapse (Aic) Pollution Of A Star...mentioning
confidence: 99%
“…Gull et al (2018) claimed that this object was the first bona fide CEMP-r+s star as its abundance pattern could be satisfactorily fitted only with AGB mass-transfer model taking into account initial r-process enhancement. Sbordone et al (2020) reported the abundance analysis of object GIU J190734.24-315102.1 located in the Sagittarius (Sgr) dwarf spheroidal (dSph) galaxy, and claimed that the abundance pattern could be best fit only with a model considering AGB-pollution in a binary system preenriched with a neutron star-neutron star merger event. Sbordone et al (2020) classify this object as the first CEMP-r/s star found in the Sgr dSph, but due to its formation scenario this object may be referred to as a bona fide CEMP-r+s star.…”
Section: Agb and Accretion-induced Collapse (Aic) Pollution Of A Star...mentioning
confidence: 99%
“…Gull et al (2018) claimed that this object was the first bona fide CEMP-r+s star as its abundance pattern could be satisfactorily fitted only with AGB mass-transfer model taking into account initial r-process enhancement. Sbordone et al (2020) reported the abundance analysis of object GIU J190734.24-315102.1 located in the Sagittarius (Sgr) dwarf spheroidal (dSph) galaxy, and claimed that the abundance pattern could be best fit only with a model considering AGB-pollution in a binary system pre-enriched with a neutron star-neutron star merger event. Sbordone et al (2020) classify this object as the first CEMP-r/s star found in the Sgr dSph, but due to its formation scenario this object may be referred to as a bona fide CEMP-r+s star.…”
Section: Formation Scenarios Of Cemp-(s and R/s) Stars And Their Like...mentioning
confidence: 99%